Pengaruh Computer Self Efficacy (CSE) Terhadap Computational Thinking Siswa Pada Mata Pelajaran Informatika di SMP Negeri 1 Salatiga - Siti Nur Afiah; Angela Atik Setiyanti; Krismiyati Krismiyati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Informatics subjects are subjects that study ICT content extensively or broadly. In informatics subjects students often use computer devices. Computer Self Efficacy (CSE) namely self-confidence in operating a computer. CSE as one of the most important variables in the field of information technology. CSE plays an important role in informatics subjects. A good CSE supports students in informatics learning activities. Computational thinking as a way to solve a complex problem by applying computational methods and concepts in computer science. This research was conducted to determine the effect of computer self-efficacy (CSE) on students' computational thinking in informatics subjects. The research method used in this study was a quantitative inferential method with a sample of 259 respondents. The research was conducted at SMP Negeri 1 Salatiga. Based on the results of the research that has been carried out, it is known that CSE has an influence on students'.